Streamlining cross-organisation product design in aeronautics. (October 2017) - Baalbergen, Erik; Kos, Johan; Louriou, Clément; Campguilhem, Cédric; Barron, James
Aircraft development programmes generally involve collaboration in engineering between different organisations, in order to develop innovative products efficiently, to involve necessary skills from the supply chain, and to spread risks and costs among the partners. The size and complexity of the programmes, the market demands and the contexts of competition all require the collaboration to be effective and efficient. Advances in information technology provide new capabilities to support collaborative design but a step change is needed to harness and coordinate this support to be effective and efficient. The extended enterprises in which the collaborative engineering activities take place span the partner organisations. Engineers wishing to cooperate are however facing security constraints. For example, technical security measures such as firewalls and proxy servers hamper smooth exchange of engineering data and seamless execution of collaborative workflows. The restrictions assist organisations in protecting their assets and in remaining compliant with legislation and regulations. From a programme technical point of view, effective and efficient collaboration in this world full of security and the resulting connectivity constraints is a major challenge. This paper describes the usefulness, necessity and challenges of collaboration between multi-disciplinary specialists in aerospace engineering. It presents the 'Brics' technology that supports the realisation of cross-organisation collaborative workflows. The technology supports aircraft manufacturers and their supply chains in facing the challenges and in performing analyses of innovative aircraft designs collaboratively. This technology has emerged from past research projects, and has been further developed and successfully demonstrated in the Thermal Overall Integrated Conception of Aircraft project, a research and technology development project carried out in the Seventh Framework Programme funded by the European Union. The developed technology is illustrated in the context of a multi-partner analysis and optimisation study, which has been conducted as part of a pylon design that is subject to thermal constraints.